Consumer product safety (UN New YorkUS, 2018)
Discusses some of the gloabla consumer product safety issues, such as cross-border challenges stemming from the rise of the digitial economy and the dumping of hazardous products in developing countries. Provides information about existing initiatives the the regional and global levels to address this issue and proposes issues for discussion by member states wishing to further explore this topic.
Keywords: CONSUMER PROTECTION